Effect of Gonadotropin-Releasing Hormone Agonist Treatment upon Angiogenesis in Uterine Leiomyoma - Abulafia, Ovadia; Kleinhaus, Karine; Levi, Gabriel; Lee, Yi-Chun; Sherer, David M. (Gynecologic and obstetric investigation, 2001)
Objective: To assess the effect of gonadotropin-releasing hormone (GnRH) agonist treatment upon angiogenesis in uterine leiomyomata. Methods: Uterine leiomyomata specimens of 49 consecutive patients who underwent myomectomy or hysterectomy following presurgical treatment with (n = 23) and without (n = 26) GnRH agonist were stained immunohistochemically with antibody to factor VIII-related antigen. For each subject, age, parity, number of Lupron treatments, leiomyoma size (cm), and mean microvessel counts calculated from three fields (×400) were recorded. Differences in patient age, parity, microvessel counts and leiomyoma size between GnRH agonist treated and untreated patients were tested by unpaired Student’s t test. Differences among the various number of doses were tested by one-way ANOVA, with Bonferonni and Neuman-Keuls post hoc tests between specific dose-number groups. The relationship between microvessel counts and leiomyoma size was tested by Pearson correlation test. Multivariate stepwise regression tested the relationship between the number of Lupron doses and microvessel counts, correcting for age, parity, and leiomyoma size. p < 0.05 was considered significant. Results: Patient age and parity were similar in GnRH treated and untreated patients (mean 43.3 ± 6.6 versus 43.9 ± 7.5 years and median 2 (range 0–7) versus 1 (range 0–5), p = 0.78 and p = 0.45, respectively). Microvessel counts of leiomyomata specimens treated presurgically with GnRH agonist therapy (median 22.7, range 6.7–65.7) were not significantly different from microvessel counts of specimens without presurgical GnRH agonist treatment (median 19.8, range 6–53; p = 0.77). No correlation between leiomyoma size and microvessel counts was noted (r = 0.06, P = 0.7). Conclusion: Angiogenesis as assessed by microvessel counts in surgically removed leiomyomata is not affected by presurgical medical management with GnRH agonist therapy.